2015
DOI: 10.4040/jkan.2015.45.4.613
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Empowerment Scale for Woman with Breast Cancer

Abstract: 연구의 필요성유방암은 유방암여성 임파워먼트 측정도구 개발 및 타당화Purpose: The purpose of this study was to develop a scale to evaluate empowerment in woman with breast cancer and to examine the validity and reliability of the scale. Methods: The development process for the initial items included a literature review, interviews, and construction of a conceptual framework. The identified items were evaluated for content validity by experts, resulting in 3 factors and 48 preliminary items. Participants were 319 women with breast cancer recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The total number of researchers participating in the preliminary survey of empowerment was set to 10 based on a prior study (Park et al, 2017;Shin & Park, 2015) on instrument development, which reported that 5 to 10 researchers was the appropriate number for such a study. Data were collected during July 8 to 25, 2019.…”
Section: Validity Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of researchers participating in the preliminary survey of empowerment was set to 10 based on a prior study (Park et al, 2017;Shin & Park, 2015) on instrument development, which reported that 5 to 10 researchers was the appropriate number for such a study. Data were collected during July 8 to 25, 2019.…”
Section: Validity Testingmentioning
confidence: 99%
“…In healthcare, "empowerment" is a popular and widely used term that has garnered increased attention since the World Health Organization (1998) defined health empowerment as a process by which people can gain greater control over the decisions affecting their lives and health. Subsequently, conceptual analysis and instrument development have been performed by studies for various types of patient empowerment (Alves et al, 2018;Anderson et al, 2000Anderson et al, , 2003Ching et al, 2020;Khanian et al, 2020;Park & Park, 2013;Shin & Park, 2015). Specific and effective interventions are being actively developed based on the clear concept of empowerment appropriate for patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ÃÃ Two questionnaires were not included even though they in all probability were relevant, because the precise framing of the items were not accessible in English [35,36]. ÃÃÃ One questionnaire was not included even though it explicitly measured empowerment in cancer patients, because only the items were accessible in English [37]. 'very much') The authors do not define their use of the term empowerment component, and the heiQ entails about 10 items with few items covering each of the four components.…”
Section: Questionnaires Explicitly Assessing Empowerment In Cancer Pamentioning
confidence: 99%
“…Scored on a 5-point Likert scale, a high score indicates higher empowerment. The scale has shown good validity and reliability [29].…”
Section: Primary Outcomementioning
confidence: 98%